Molecular genetic analysis of colorectal carcinoma : Gene expression profiling and analysis of the tumour suppressor genes APC and Dcc - Bong, Ivyna Pau Ni (2005)
Colorectal carcinoma (CRC) ranks third among the ten leading causes of cancers in Malaysia (Annual Report of Cancer Incidence in Malaysia, 2002). The CRC tumourigenesis involved the inactivation of tumour suppressor genes, and activation of proto-oncogenes. Generally, colorectal adenoma is initiated by genetic aberrations in adenomatous polyposis coli (APC) gene, which cause the stabilization of ß-catenin via activation of Wnt transduction pathway. These events will eventually lead to over-expression of its downstream target genes such as Cyclin D1, c-myc, c-jun and Matrilysin, which function as cell cycle regulators, apoptotic genes and transcription factors. In this study, we report the simultaneous evaluation of gene expression profiles of Caucasian and Malaysian CRC patients using DNA microarray. The data on gene expression patterns revealed a total of 831 up-regulated genes and 103 down-regulated genes. Among the differentially expressed genes, 12 of them were verified by RT-PCR assay. They are Wnt2, Apo3, OSF-2p1, immunoglobulin lambda heavy chain, immunoglobulin heavy chain, V region, glutathione peroxidase, TYL, BBI, Mpv17, TSGI01, ribosomal protein L7a (surf3) large subunit, ribosomal protein L32 and MLC-2. Most of the differentially expressed transcripts represented novel findings (OSF-2P1, Apo3, TSG101, MPV17, MLC-2 and TYL) while some of them are coincided with existing literature (Wnt, and ribosomal protein L7). Apart from that, analysis of Deleted in Colorectal Carcinoma (DCC) gene, which plays an important role in the initiation and progression of CRC, was performed in this study. Mutational analysis of DCC gene in Asian CRC is still very limited. By using novel DCC exonic primers, mutational analysis of DCC mRNA regions in CRC was successfully carried out and results obtained revealed several mutation sites in the CRC samples examined.